1981
DOI: 10.1007/bf00346987
|View full text |Cite
|
Sign up to set email alerts
|

Moss functioning in different taiga ecosystems in interior Alaska

Abstract: Carbon dioxide exchange rates in excised 2-year-old shoot sections of five common moss species were measured by infrared gas analysis in mosses collected from different stands of mature vegetation near Fairbanks, Alaska. The maximum rates of net photosynthesis ranged from 2.65 mg CO gh in Polytrichum commune Hedw. to 0.25 in Spagnum nemoreum Scop. Intermediate values were found in Sphagnum subsecundum Nees., Hylocomium splendens (Hedw.) B.S.G., and Pleurozium schreberi (Brid.) Mitt. Dark respiration rates at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0
1

Year Published

1987
1987
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(47 citation statements)
references
References 19 publications
5
41
0
1
Order By: Relevance
“…This result is consistent with the absence of a significant interaction between treatment and DOY for SGR (Table 3). In both treated and untreated plots, Sphagnum growth was stimulated by elevated soil temperatures and dry conditions, a result that has been documented previously (Skre and Oechel 1981;Sonesson et al 2002;Dorrepaal et al 2004Dorrepaal et al , 2006Gunnarsson 2005;Breeuwer et al 2008;Lang et al 2009). However, we did not see a significant difference in soil moisture between treatments.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This result is consistent with the absence of a significant interaction between treatment and DOY for SGR (Table 3). In both treated and untreated plots, Sphagnum growth was stimulated by elevated soil temperatures and dry conditions, a result that has been documented previously (Skre and Oechel 1981;Sonesson et al 2002;Dorrepaal et al 2004Dorrepaal et al , 2006Gunnarsson 2005;Breeuwer et al 2008;Lang et al 2009). However, we did not see a significant difference in soil moisture between treatments.…”
Section: Discussionsupporting
confidence: 73%
“…Previous studies from interior Alaska have shown that the positive effect of a rain event depends on the length of the preceding dry period (Skre and Oechel 1981). Therefore, the proportion of dry days (PDD), that is, days without precipitation, was computed.…”
Section: Environmental Datamentioning
confidence: 99%
“…Such knowledge is important in view of the consequences of possible future climatic changes : higher atmospheric CO # concentrations will be followed by from desiccation ; and in response to repeated desiccation. Earlier studies (Skre & Oechel, 1981 ;Titus, Wagner & Stephens, 1983 ;Silvola & Aaltonen, 1984 ;Rydin & McDonald, 1985 b ;Murray et al, 1989) showed no general differences in photosynthetic response to low tissue water contents between hummock and hollow species, and differences in desiccation tolerance seemed not to be related to the natural microhabitat of the species (Clymo, 1973 ;Sagot & Rochefort, 1996). This study concentrates on the effects of repeated desiccation.…”
Section: mentioning
confidence: 93%
“…Recovery of net photosynthesis after repeated desiccation (1997) Recovery was rather poor in Experiment 1, so a different design was used to test the effect of repeated desiccation. To imitate alternating wetting-drying cycles, the complete moss carpet in the plastic cylinders in the growth chamber was allowed to dry out several times for 60 h and in between was rewetted for 12 h. The capitula were cut before rewetting and gas exchange measurements were made (Skre & Oechel, 1981). New capitula from the moss-cylinders were used for each measurement.…”
Section: Experiments 1 Recovery Of Net Photosynthesis After Repeated mentioning
confidence: 99%
“…Though Robroek et al (2007b) did find greater height increment and production at 20°C than at 15°C for several Sphagnum species, their experiment lasted for only 6 months. Harley et al (1989) and Skre and Oechel (1981) showed that photosynthesis in Sphagnum increases with temperature up to an optimum around 20-25°C. The absence of a response to temperature in our experiment may indicate that the maximum photosynthetic rates of Sphagnum were already reached at the average temperatures of 17.4 and 21.7°C we used.…”
Section: Temperaturementioning
confidence: 99%